AKTUALISASI CIVIC CULTURE DALAM TRADISI MAHANYARI BARAS DI DESA ALUH-ALUH BESAR KECAMATAN ALUH-ALUH - Yulianti, Nursyifa; Mariatul Kiptiah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Civic culture is the concept of the importance of community participation in collective welfare embodied in the mahanyari baras tradition. Elements of civic culture, such as social networking, solidarity, and participation, are considered important to be actualized, so that they are not merely a matter of reason alone but also become the basis for good behavior in society. This study aims to understand the process of the mahanyari baras tradition while analyzing its civic culture. The method used is qualitative with purposive sampling. Data collection techniques include observation, interviews, and documentation, followed by analysis through data presentation, data reduction, and drawing conclusions. The results show that the mahanyari baras tradition process consists of planning including a series of harvest activities until the paddy becomes rice, as well as providing tools and materials to carry out the mahanyari baras tradition. The tradition’s implementation includes reciting prayers and eating together. The final result of this traditional activity is the distribution of hanyar rice to those in need. Elements of civic culture such as social networking, solidarity, and participation are also evident in this tradition. This is seen through various forms of togetherness, cooperation, and a sense of responsibility for the common good that grow from the existence of this tradition in the community.